2012
DOI: 10.1080/09670262.2012.717106
|View full text |Cite
|
Sign up to set email alerts
|

The subaerophytic cyanobacteriumOculatella subterranea(Oscillatoriales, Cyanophyceae)gen. et sp. nov.: a cytomorphological and molecular description

Abstract: A new genus and species of subaerophytic cyanobacteria with very thin purple-red trichomes are described. The seven strains included in this genus were isolated from phototrophic biofilms growing on calcareous substrata in ancient hypogea. Trichomes were 1-3 mm thick, with small constrictions at the cross-walls and colourless sheaths. The thylakoid arrangement was parietal. Autapomorphic characters include the purple-red colouration of cells and a photosensitive orange spot at the tip of the trichome containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(88 citation statements)
references
References 40 publications
5
72
0
1
Order By: Relevance
“…The genus Oculatella (Zammit et al, 2012) and the species Oculatella subterranea, was established after the study of some Roman and Maltese catacombs applying a combination of both morphological and molecular data. The main morphological features of Oculatella are the red-purple coloration of cells and the presence of an orange photoreceptive structure at the trichomes tips.…”
Section: Discussionmentioning
confidence: 99%
“…The genus Oculatella (Zammit et al, 2012) and the species Oculatella subterranea, was established after the study of some Roman and Maltese catacombs applying a combination of both morphological and molecular data. The main morphological features of Oculatella are the red-purple coloration of cells and the presence of an orange photoreceptive structure at the trichomes tips.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, with higher resolution abilities, we can expect a further expansion of the number of described taxa. For example, Oculatella erected with single species (Zammit et al 2012) now contains seven species, which have been described by different researchers. Thus, even the most liberal estimates may be undervalued.…”
Section: Estimate Of the Total Cyanobacterial Biodiversitymentioning
confidence: 99%
“…Unfortunately, this circumscription is so broad that numerous genetically distinct strains and species were assigned to Leptolyngbya based on morphology, even though recent phylogenetic studies have demonstrated that the genus is polyphyletic and in need of taxonomic revision , Osorio-Santos et al 2014. This revisionary work has commenced, and over a dozen novel genera have been split out of Leptolyngbya thus far (Abed et al 2002, Turicchia et al 2009, Perkerson et al 2011, Taton et al 2011, Zammit et al 2012, Dadheech et al 2012, Vaz et al 2015, Song et al 2015a, 2015b, Miscoe et al, 2016, Sciuto et Moro 2016, Sciuto et al 2017, Strunecký et al 2017.…”
Section: Introductionmentioning
confidence: 99%